2001
DOI: 10.1097/00000658-200107000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preoperative Biliary Decompression on Pancreaticoduodenectomy-Associated Morbidity in 300 Consecutive Patients

Abstract: Preoperative biliary decompression increases the risk for postoperative wound infections after pancreaticoduodenectomy. However, there was no increase in the risk of major postoperative complications or death associated with preoperative stent placement. Patients with extrahepatic biliary obstruction do not necessarily require immediate laparotomy to undergo pancreaticoduodenectomy with acceptable morbidity and mortality rates; such patients can be treated by endoscopic biliary drainage without concern for inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
162
3
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(177 citation statements)
references
References 30 publications
8
162
3
4
Order By: Relevance
“…4,51 Pisters et al brought this argument up to justify PBD to create time for referral of patients to highvolume tertiary surgical centers, their (retrospective) study did not demonstrate an increase in the risk of major postoperative complications associated with PBD and stent placement. 52,53 Logistics in terms of (local) referral patterns, waiting lists, extended diagnostic workup with laparoscopy (on indication), or scheduled preoperative chemotherapy could be other plausible factors that might influence the decision to opt for PBD. Possibly, these factors are region-specific for, at least in the USA, in the eastern part of the country, early surgery without drainage is strongly advocated, whereas in the southern part, PBD is favored.…”
Section: Pbd For Distal Obstructionmentioning
confidence: 99%
“…4,51 Pisters et al brought this argument up to justify PBD to create time for referral of patients to highvolume tertiary surgical centers, their (retrospective) study did not demonstrate an increase in the risk of major postoperative complications associated with PBD and stent placement. 52,53 Logistics in terms of (local) referral patterns, waiting lists, extended diagnostic workup with laparoscopy (on indication), or scheduled preoperative chemotherapy could be other plausible factors that might influence the decision to opt for PBD. Possibly, these factors are region-specific for, at least in the USA, in the eastern part of the country, early surgery without drainage is strongly advocated, whereas in the southern part, PBD is favored.…”
Section: Pbd For Distal Obstructionmentioning
confidence: 99%
“…The pre-operative drainage group included 172 patients who were stented and 35 patients who had undergone a surgical bypass prior to referral. 45 Although wound sepsis was higher in the stented group, there was no difference in terms of overall complications or mortality which was 1%. They concluded that pre-operative biliary drainage is safe and does not increase risk in patients with obstructive jaundice and allows neo-adjuvant therapy to be administered.…”
Section: The Clinical Datamentioning
confidence: 85%
“…[39][40][41][42] However, there are large volume centres who have data to support the contention that pre-operative drainage is not necessarily a bad thing (Table 4). [45][46][47] Sohn et al 44 reviewed 567 patients who had been subjected to pancreaticoduodenectomy. There were no differences in intra-operative physiological behaviour and mortality rates between the two groups were similar.…”
Section: The Clinical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Conflicting data regarding the effect of preoperative biliary drainage and its relationship with perioperative complications has been published in the past decade [10][11][12][13]. In our institution, the decision to stent is always made in conjunction with the involved specialists, such as the surgeons and oncologists, after tumor staging has occurred.…”
mentioning
confidence: 99%